NusG-Dependent RNA Polymerase Pausing and Tylosin-Dependent Ribosome Stalling Are Required for Tylosin Resistance by Inducing 23S rRNA Methylation in Bacillus subtilis - Helen Yakhnin (American Society for Microbiology, 2019)
ABSTRACT Macrolide antibiotics bind to 23S rRNA within the peptide exit tunnel of the ribosome, causing the translating ribosome to stall when an appropriately positioned macrolide arrest motif is encountered in the nascent polypeptide. Tylosin is a macrolide antibiotic produced by Streptomyces fradiae. Resistance to tylosin in S. fradiae is conferred by methylation of 23S rRNA by TlrD and RlmAII. Here, we demonstrate that yxjB encodes RlmAII in Bacillus subtilis and that YxjB-specific methylation of 23S rRNA in the peptide exit tunnel confers tylosin resistance. Growth in the presence of subinhibitory concentrations of tylosin results in increased rRNA methylation and increased resistance. In the absence of tylosin, yxjB expression is repressed by transcription attenuation and translation attenuation mechanisms. Tylosin-dependent induction of yxjB expression relieves these two repression mechanisms. Induction requires tylosin-dependent ribosome stalling at an RYR arrest motif at the C terminus of a leader peptide encoded upstream of yxjB. Furthermore, NusG-dependent RNA polymerase pausing between the leader peptide and yxjB coding sequences is essential for tylosin-dependent induction. Pausing synchronizes the position of RNA polymerase with ribosome position such that the stalled ribosome prevents transcription termination and formation of an RNA structure that sequesters the yxjB ribosome binding site. On the basis of our results, we are renaming yxjB as tlrB. IMPORTANCE Antibiotic resistance is a growing health concern. Resistance mechanisms have evolved that provide bacteria with a growth advantage in their natural habitat such as the soil. We determined that B. subtilis, a Gram-positive soil organism, has a mechanism of resistance to tylosin, a macrolide antibiotic commonly used in the meat industry. Tylosin induces expression of yxjB, which encodes an enzyme that methylates 23S rRNA. YxjB-dependent methylation of 23S rRNA confers tylosin resistance. NusG-dependent RNA polymerase pausing and tylosin-dependent ribosome stalling induce yxjB expression, and hence tylosin resistance, by preventing transcription termination upstream of the yxjB coding sequence and by preventing repression of yxjB translation.